RITUAL TABOT PROVINSI BENGKULU SEBAGAI MEDIA DAKWAH ANTAR BUDAYA - Siroy Kurniawan; Ririn Jamiah (Jurnal Komunikasi dan Budaya, 2022)
The history of the development of Islam in Indonesia has a very long story. Starting from the spread through trade, colonialism, empire, to culture. Various kinds of traditions, traditional rituals, culture and diversity rituals have a different style in each area that is widespread in Indonesia. A cultural ritual wrapped in religious nuances in Indonesia is very many, even in each region must have cultural nuances of religion with their respective characteristics. The spread of Islam through culture is not taboo. Such as inviting religious ritual activities in the month of Muharam. In the treasury of Islamic history, the month of Muharram becomes more valuable, because it becomes the first month in the Hijri calendar. As with books close and open books, as well as charity. Muharram is a month that has long been known since pre-Islam. Then at the time of the Prophet until Umar bin Khattab was inaugurated as a fixed calendar of Islam. In the sense that the month of Muharam is a sacred month of Islamic history. Like when celebrating Tabot in the city of Bengkulu, combining elements of Islam and cultivation that blend into one with unity. Tabot ritual itself is a form of activity carried out by the people of Bengkulu city. This ritual is held for 10 days, carried out from 1 to 10 Muharam. The meaning of the tabot ritual has two steps, first, the tabot celebration is interpreted as a form of resistance to the death of Husein bin Ali on the 10th of Muharam. While the second element is relying on symbols and traditions, thus the Ark is also nuanced in local culture, cannot be used. Mean